The Interface Between ER and Mitochondria: Molecular Compositions and Functions - Lee, Soyeon; Min, Kyung-Tai (Molecules and cells, 2018)
Mitochondria and endoplasmic reticulum (ER) are essential organelles in eukaryotic cells, which play key roles in various biological pathways. Mitochondria are responsible for ATP production, maintenance of Ca homeostasis and regulation of apoptosis, while ER is involved in protein folding, lipid metabolism as well as Ca homeostasis. These organelles have their own functions, but they also communicate via mitochondrial-associated ER membrane (MAM) to provide another level of regulations in energy production, lipid process, Ca buffering, and apoptosis. Hence, defects in MAM alter cell survival and death. Here, we review components forming the molecular junctions of MAM and how MAM regulates cellular functions. Furthermore, we discuss the effects of impaired ER-mitochondrial communication in various neurodegenerative diseases.